Growth trajectories of some major ammonoid sub‐clades revealed by serial grinding tomography data. (7th July 2014) - Naglik, Carole; Monnet, Claude; Goetz, Stefan; Kolb, Christian; De Baets, Kenneth; Tajika, Amane; Klug, Christian
<x xml:space="preserve">Abstract</x> Molluscs such as ammonoids record their growth in their accretionary shells, making them ideal for the study of evolutionary changes in ontogeny through time. Standard methods usually focus on two‐dimensional data and do not quantify empirical changes in shell and chamber volumes through ontogeny, which can possibly be important to disentangle phylogeny, interspecific variation and palaeobiology of these extinct cephalopods. Tomographic and computational methods offer the opportunity to empirically study volumetric changes in shell and chamber volumes through ontogeny of major ammonoid sub‐clades in three dimensions (3‐D). Here, we document (1) the growth of chamber and septal volumes through ontogeny and (2) differences in ontogenetic changes between species from each of three major sub‐clades of Palaeozoic ammonoids throughout their early phylogeny. The data used are three‐dimensional reconstructions of specimens that have been subjected to grinding tomography. The following species were studied: the agoniatitid Fidelites clariondi and anarcestid Diallagites lenticulifer (Middle Devonian) and the Early Carboniferous goniatitid Goniatites multiliratus. Chamber and septum volumes were plotted against the septum number and the shell diameter (proxies for growth) in the three species; although differences are small, the trajectories are more similar among the most derived Diallagites and Goniatites compared with the more widely umbilicate Fidelites. Our comparisons show a good correlation between the 3‐D and the 2‐D measurements. In all three species, both volumes follow exponential trends with deviations in very early ontogeny (resolution artefacts) and near maturity (mature modifications in shell growth). Additionally, we analyse the intraspecific differences in the volume data between two specimens of Normannites (Middle Jurassic).